Psychosocial determinants of healthcare use costs in kidney transplant recipients - Zerbinati, Luigi; Guerzoni, Franco; Napoli, Nicola; Preti, Antonio; Esposito, Pasquale; Caruso, Rosangela; Bulighin, Francesca; Storari, Alda; Grassi, Luigi; Battaglia, Yuri (Frontiers in Public Health, 2023)
Introduction Psychosocial factors frequently occur in kidney transplant recipients (KTRs), leading to behavioral alterations and reduced therapeutic adherence. However, the burden of psychosocial disorders on costs for KTRs is unknown. The aim of the study is to identify predictors of healthcare costs due to hospital admissions and emergency department access in KTRs. Methods This is a longitudinal observational study conducted on KTRs aged >18 years, excluding patients with an insufficient level of autonomy and cognitive disorder. KTRs underwent psychosocial assessment via two interviews, namely the Mini-International Neuropsychiatric Interview 6.0 (MINI 6.0) and the Diagnostic Criteria for Psychosomatic Research Interview (DCPR) and via the Edmonton Symptom Assessment System Revised (ESAS-R) scale, a self-administrated questionnaire. Sociodemographic data and healthcare costs for hospital admissions and emergency department access were collected in the 2016–2021 period. Psychosocial determinants were as follows: (1) ESAS-R psychological and physical score; (2) symptomatic clusters determined by DCPR (illness behavior cluster, somatization cluster, and personological cluster); and (3) ICD diagnosis of adjustment disorder, anxiety disorder, and mood disorder. A multivariate regression model was used to test the association between psychosocial determinants and total healthcare costs. Results A total of 134 KTRs were enrolled, of whom 90 (67%) were men with a mean age of 56 years. A preliminary analysis of healthcare costs highlighted that higher healthcare costs are correlated with worse outcomes and death (p < 0.001). Somatization clusters (p = 0.020) and mood disorder (p < 0.001) were positively associated with costs due to total healthcare costs. Conclusions This study showed somatization and mood disorders could predict costs for hospital admissions and emergency department access and be possible risk factors for poor outcomes, including death, in KTRs.